Tissue reactions to primers used in "single-step" orthodontic bonding system - Reyes, Beth M.; Sevilleja, Ma. Isabella Esperanza A.D.; Eustaquio, Robert I. (Adviser).
In recent years, "single-step" bonding systems was introduced in the field of orthodontics for the direct bonding of brackets to enamel of teeth. A number of studies have questioned the biocompatibility of some of the direct bonding materials used in orthodontic practices. It is the purpose of this study to determine the reaction of tissues to primers used in "single-step" orthodontic bonding system among individuals newly exposed and individuals with prolonged exposure to the material, with and without allergic predisposition. The primers used in this study are Alpha-dent and right on. A survey of first year and fourth year students from the U.P. College of Dentistry characterized those having allergic predisposition from those who have not. Patch testing was then preformed on the students where the patches were retained on the subjects skin for 24 hours. Results of the reaction on the tissues to the primers were then reported 20 minutes, 60 minutes, and 120 minutes after the patches were removed. The results indicated a significant difference in terms of tissue reaction between those with allergic predisposition and those without allergic predisposition for each group. Furthermore, a general trend of a greater tissue response among those who are newly exposed to the material as against those who have prolonged exposure to the material was shown.
Seminar Paper--Doctor of Dental Medicine--University of the Philippines Manila.
Keywords: Orthodontics; Dental materials